Research on Hot-spots and Trends of Human Resource Management under Digitalization - Lin Haitianyu; Wu Di (SHS Web of Conferences, 2024)
A new era of digital technology, characterized by the advent of mobile internet, cloud computing, big data, and artificial intelligence, is reshaping human production and lifestyle, heralding a paradigm shift in the way we engage with the world around us. As a matter of fact, digital transformation is no longer a distant future but an ongoing reality faced by all enterprises alike. Within this evolving landscape, human resources management, being a pivotal component of organizational management, is undergoing profound changes driven by digitalization. This paper combs the literature from all over the world in the field of digital human resource management in the past ten years, and extracts the key discoveries. This paper sums up the four most popular research topics: digital natives, service-oriented human resource management, updated connection mode, and ensuring the status of humanity. On the basis of the review, this paper looks forward to the future by pointing out possible research directions and making relevant recommendations.